THE ESTIMATION OF PHYTOTOXIC ACTION OF WASTEWATER IN WASTE DISPOSAL SITES ON TRITICUM AESTIVUM RESISTANCE - Pysarenko, P. V.; Samoilik, M. S.; Dychenko, O. Yu.; Korchahin, O. P.; Molchanova, A. V. (Scientific Progress & Innovations, 2019)
Anthropogenic pollution of the environment results in the degradation of ecological systems, global climatic and geochemical changes as well as regional and local ecological crises and disasters. So, we have chosen to investigate specific characteristics of the toxic impact of sewage water in waste disposal sites on the resistance of Triticum aestivum and to develop the methods of polluted soil reclamation in hazardous waste dumps to return the soil into economic circulation. As a result of our research, the assessment of the impact of waste disposal sites on biota was made by determining the phytotoxic influence of the polluted soil and sewage water on the germination, vegetation and the root system of Triticum aestivum. It was found out that in the soil, collected on a solid domestic waste landfill, the germination of sprouted plants is 16 % less, in comparison with the control (clean soil); the aerial part of plant length is 22 % less, the average length of roots is 44 % less. The stalk weight and the root system weight of plants in the soil taken from the dump are 52 % and 43 % smaller respectively. It was determined that after adding the “Sviteco-PBG” probiotic (10% solution) to contaminated soil, the germination of sprouted plants was 5.2 % better than in the contaminated soil without adding the probiotic, the stem length increased by 11.6 % and the average root length increased by 40.2 %, respectively; the weight of the aerial part and the weight of the plant root system were bigger by 14 % and 16.5 % as compared with the contaminated soil without adding the probiotic. Thus, using probiotics can significantly improve the soil quality and reduce its phyto-toxicity, in particular, if the impact on the root system of contaminated soil was characterized as higher than the average value of toxicity and after using probiotics the toxicity was either absent (weak) concerning the root length or average concerning the root weight. It was established that in case of adding “Sviteco-PBG” probiotic (10 % solution) and Ca(OH)2 into wastewater in the solid domestic waste dump at pH 10, the purification of this wastewater from heavy metals reached their maximum. At the same time, phytotoxic effect of the polluted filtrate without purification was higher than the average value of toxicity. Thus, the using of probiotics can significantly improve the effectiveness of soil purification from heavy metals, which gives the opportunity of returning the contaminated land to tillage in the future. The use of Ca(OH)2 and the “Sviteco-PBG” probiotic (10 % solution) at pH 10 can significantly improve the quality of contaminated soils as a result of anthropogenic impact as well as reduce the toxic effects on biota and increase the effectiveness of sewage water purification in waste disposal sites.